Metastatic mineralisation caused by vitamin D intoxication in hand‐raised short‐beaked echidnas (Tachyglossus aculeatus). Issue 11 (27th October 2017) - Scheelings, TF; Slocombe, RF; Bayley, C
Abstract : Case report: Two cases of metastatic mineralisation caused by dietary excess of vitamin D are reported in hand‐raised short‐beaked echidna ( Tachyglossus aculeatus ) puggles at the Australian Wildlife Health Centre. Oversupplementation was attributed to excessive levels of vitamin D in Wombaroo Echidna Milk Replacer fed to the puggles. No information exists regarding the naturally occurring vitamin D levels in echidna milk, but, given the low serum levels that have been observed in free‐ranging animals, it is likely to be low. Conclusion: The vitamin D concentration in Wombaroo Echidna Milk Replacer has been reduced.